Actuality and potentiality in Dignāga’s understanding of immediate perception (nirvikalpaka pratyakṣa) according to his Pramāṇasamuccaya and Ālambanaparīkṣā - Lysenko, Viktoria (Acta Orientalia Vilnensia, 2010)
Institute of Philosophy, Russian Academy of SciencesOn the one hand, Dignāga supposes in his Pramāṇasamuccaya (part 1) that immediate perceptual experience at every given moment has as its object something that never goes beyond its own actually present content and thus may characterise only itself (svalakṣaṇa). In that respect, svalakṣaṇa appears as a kind of mere presence, sheer momentary actuality. It cannot undergo any external influence or exercise its own influence on other svalakṣaṇas. In other words, it cannot be extended to things other than itself, as is the case of mental constructions. First, I would like to ask whether there is a potentiality in the act of immediate perception according to the Pramāṇasamuccaya. On the other hand, in the Ālambanaparīkṣā, cognition is an entirely interior process manifests itself as a sense organ to an internal cognisable form. Second, I would like to dwell on the question concerning whether an immediate perception of svalakṣaṇas, free from mental constructions, is still possible in the Ālambanaparīkṣā.